The Pavlovian interpretation of speech and aphasia: Alexander Luria and Wilder Penfield - Leblanc, Richard (Frontiers in Psychology, 2024)
This paper discusses a neglected aspect of the historiography of aphasia, the role that Pavlovian conditioning played in Alexander Luria's and Wilder Penfield's understanding of the acquisition, expression, and loss of spoken and written speech. Luria was born into a bourgeois family in Tzarist Russia and pursued his research on speech and aphasia under the Soviet regime. Luria's work was condemned in the last years of Stalin's rule, but it received international acclaim in the West upon Stalin's death. Penfield was conversant with Pavlov's writing having had a working relationship with one of Pavlov's foremost students, Boris Babkin, who came to McGill University and later to the Montreal Neurological Institute after being jailed and exiled from the Soviet Union for lack of revolutionary fervor. Both Luria and Penfield, the latter as early as 1935, saw in Pavlovian conditioning mediated by specific areas of the human cerebral cortex the basic neurophysiological mechanism underlying speech and thought, and in Penfield's' case, memory, perception, self-awareness, and purposeful behavior. It is concluded that Luria and Penfield independently arrived at a general hypothesis, based on Pavlovian conditioning, that united the localization of speech, the syndromes caused by damage to speechcompetent regions, and the putative neurophysiological mechanisms that they believed to underlie speech and higher cortical functions.